"Югдонын" зардэ: Роман / Генрих Перевощиков - Перевощиков Генрих Ксенофонтович (Удмуртия, 1980)
Экземпляры: ф.3 (20170828) / Инвентарный номер: 03006 / Цена: 1.20 / Авт.знак: П 27 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Удм)6